Study On Poly Vinyl Chloride Based Sensor For Anion Recognition Using 1 12 diaaza 5 8 dioxo 3 4 10 dibenzoylcyclotetradeca 2 11 diene L1[DADODBCT Schiff Based Macrocyclic Receptor - Nagar, Amit (International Journal of Pharmaceutical & Biological Archive, 2014)
Study On Poly Vinyl Chloride Based Sensor For Anion Recognition Using 1 12 diaaza 5 8 dioxo 3 4 10 dibenzoylcyclotetradeca 2 11 diene L1[DADODBCT Schiff Based Macrocyclic Receptor